Empirical superior vena cava isolation improves outcomes of radiofrequency re-ablation in pulmonary vein isolation non-responders: A 2-center retrospective study in China - Gu, Zhoushan; Yang, Gang; Ju, Weizhu; Li, Mingfang; Chen, Hongwu; Gu, Kai; Liu, Hailei; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Pulmonary vein isolation (PVI) is the standard ablation strategy for treating atrial fibrillation (AF). However, the optimal strategy of a repeat procedure for PVI non-responders remains unclear. OBJECTIVE: This study aims to investigate the incidence of PVI non-responders in patients undergoing a repeat procedure, as well as the predictors for the recurrence of repeat ablation. METHODS: A total of 276 consecutive patients who underwent repeat ablation from August 2016 to July 2019 in two centers were screened. A total of 64 (22%) patients with durable PVI were enrolled. Techniques such as low voltage zone modification, linear ablation, non-PV trigger ablation, and empirical superior vena cava (SVC) isolation were conducted. RESULTS: After the 20.0±9.9 month follow-up, 42 (65.6%) patients were free from atrial arrhythmias. A significant difference was reported between the recurrent and non-recurrent groups in non-paroxysmal AF (50% vs. 23.8%, p=0.038), diabetes mellitus (27.3% vs. 4.8%, p=0.02), and empirical superior vena cava (SVC) isolation (28.6% vs. 60.5%, p=0.019). Multivariate regression analysis demonstrated that empirical SVC isolation was an independent predictor of freedom from recurrence (95% CI: 1.64–32.8, p=0.009). Kaplan-Meier curve demonstrates significant difference in recurrence between empirical and non-empirical SVC isolation groups (HR: 0.338; 95% CI: 0.131-0.873; P=0.025). CONCLUSION: About 22% of patients in repeat procedures were PVI non-responders. Non-paroxysmal AF and diabetes mellitus were associated with recurrence post-re-ablation. Empirical SVC isolation could potentially improve the outcome of repeat procedures in PVI non-responders.